Uma nova ecologia da aprendizagem: a nova ecologia midiática e a incorporação das tecnologias digitais na educação - Souza, Maria Eliane de (2016)
The objective of this research was to investigate the pedagogical use of Information and Communication Digital Technologies (TDIC), teachers and students from public schools in the city of São Paulo Education (RME). We conducted a qualitative study we applied questionnaires to RME's students and teachers of. Established categories of analysis that emerged from the interpretation of the data. This research has the theoretical framework in studies of Postman (1970; 2000) and McLuhan (1969, 2010), who study very properly ecology media. Castells (2003), which analyzes the knowledge society by stating that it is a society of multiple learning opportunities and for the first time the human mind is a direct productive force. Basbaum (2005) and his studies on the reorganization of the senses through technologies. Alegretti (2012) helps to analyze the extended school through mobile technologies. We read and Di Felice (2014), dealing with very domain, the contemporary cultural context reticular structured in media networks that enable the network dialog. Coll (2013), which proposes the concept of a new ecology of learning arising from digital technologies of information and communication. We found that the objectives of this study were achieved by identifying the inherent technological artifacts of the new media ecology, which are in use by students and public school teachers of RME of São Paulo and the TDIC mediation potential for effective integration and transformation of the school curriculum